Determining E-Government Trust: An Information Systems Success Model Approach to the Philippines’ Government Service Insurance System (GSIS), the Social Security System (SSS), and the Bureau of Internal Revenue (BIR) - Capistrano, Erik Paolo (Philippine Management Review; Vol 27 (2020), 2021)
Building trust in e-government is not easy, especially in a country that faces many contextual, technological, and social challenges. This discourse on Philippine e-government is an ongoing one, as many of these initiatives are piecemeal in the various branches and levels of government. This research particularly looks at three e-government platforms rendering some mandated financial services to the citizens: (1) social security services provided by the Government Service Insurance System (GSIS) and the Social Security System (SSS), and (2) tax services delivered by the Bureau of Internal Revenue (BIR). Employing a theoretical framework based on interpretations of the Information Systems Success Model and trust building towards e-government, data collected from a total of 668 respondents across the three government institutions are subjected to structural equation modeling to determine what factors influence trust in e-government. The results show that trust in technology and information quality perceptions are the most significant determinants of trust in egovernment, while there are some concerns regarding system quality in building trust in egovernment. Further implications and recommendations are also included in this research.